Digital photography for dummies - King, Julie Adair (-- For dummies, 2012)
Book Description: Publication Date: March 27, 2012 - Series: Digital Photography for Dummies. A new edition gets you in the picture for learning digital photography. Whether you have a point-and-shoot or digital SLR camera, this new edition of the full-color bestseller is packed with tips, advice, and insight that you won't find in your camera manual. Digital photography guru Julie Adair King presents you with new and extensively updated information on topics that is written for fledgling photographers in a fun and friendly style. You'll explore tips for finding the gear that best suits your needs, using built-in tools, working with focus and exposure, and shooting like a pro. However, if you've already got an archives full of photos, then this guide shows you how to upload, edit, manage, and share your images. Advice for prolonging battery life, an honest look at the pros and cons of digital SLR, and a helpful glossary are all aimed at making your experience with digital photography picture perfect! Shows you how to set up your camera for basic shooting and use automatic mode, common scene modes, and all the camera's features. Explains how to edit your images and fix common problems like dim lighting or red-eye. Highlights ways to print photos at home or through a service and then posting online to social sites or send to a cell phone. Helps you manage depth of field, exposure, and white balance. Digital Photography For Dummies, 7th Edition provides you with rich, full-color examples throughout to help your digital pictures say more than a thousand words!